A Novel Strategy of In Situ Trimerization of Cyano Groups Between the Ti3C2Tx (MXene) Interlayers for High-Energy and High-Power Sodium-Ion Capacitors - Liu, Siyang; Hu, Fangyuan; Shao, Wenlong; Zhang, Wenshu; Song, Ce; Yao, Man; Huang, Hao; Jian, Xigao (Nano-Micro Letters, 2020)
2D MXenes are attractive for energy storage applications because of their high electronic conductivity. However, it is still highly challenging for improving the sluggish sodium (Na)-ion transport kinetics within the MXenes interlayers. Herein, a novel nitrogen-doped Ti3C2Tx MXene was synthesized by introducing the in situ polymeric sodium dicyanamide (Na-dca) to tune the complex terminations and then utilized as intercalation-type pseudocapacitive anode of Na-ion capacitors (NICs). The Na-dca can intercalate into the interlayers of Ti3C2Tx nanosheets and simultaneously form sodium tricyanomelaminate (Na3TCM) by the catalyst-free trimerization. The as-prepared Ti3C2Tx/Na3TCM exhibits a high N-doping of 5.6 at.% in the form of strong Ti–N bonding and stabilized triazine ring structure. Consequently, coupling Ti3C2Tx/Na3TCM anode with different mass of activated carbon cathodes, the asymmetric MXene//carbon NICs are assembled. It is able to deliver high energy density (97.6 Wh kg−1), high power output (16.5 kW kg−1), and excellent cycling stability (≈ 82.6% capacitance retention after 8000 cycles). Highlights: 1 A novel N-doped strategy of C2N3− in situ trimerization between the 2D MXene interlayers was first proposed. 2 The ultra-fast pseudocapacitive behavior of Ti3C2Tx/Na3TCM anode was managed and verified. 3 The as-fabricated sodium-ion capacitor delivers excellent electrochemical performance by anode/cathode mass matching.